Enhancing EFL Students’ Writing Performance through Inquiry Based Learning - Derseh, Bantalem (ITALIAN JOURNAL OF EDUCATIONAL RESEARCH, 2020)
The aim of this study was to enhance students’ writing performance through inquiry based learning. A quasi-experimental design which employed Time Series Design with single group participants was used. A total of 20 EFL undergraduate students were selected using comprehensive sampling method. Tests, focus group discussion, and student-reflective journal were used to gather data on the students’ writing performance. The participants were given a series of three argumentative essay writing pretests both before and after the intervention, inquiry based argumentative essay writing instruction. While the quantitative data were analyzed using One-Way Repeated Measures ANOVA, the qualitative data were analyzed through narration. The findings of the study revealed that using inquiry based argumentative writing instruction develop students’ writing performance. Therefore, inquiry based instruction is suggested as a means to improve students’ writing performance because the method incorporates activity oriented learning, logical arguments, and collaboration.